Comparison of the microbial communities of alpacas and sheep fed diets with three different ratios of corn stalk to concentrate. Issue 1 (7th October 2020) - Chao, Ruimin; Xia, Chengqiang; Pei, Caixia; Huo, Wenjie; Liu, Qiang; Zhang, Chunxiang; Ren, Youshe
Abstract: The objective of this study was to investigate the characteristics of ruminal microbial communities of alpacas ( Lama pacos ) and sheep ( Ovis aries ) fed three diets with varying ratios of roughage (corn stalk) to concentrate, 3:7 (LS), 5:5 (MS) and 7:3 (HS). Six alpacas (one‐year‐old and weighing 29.5 ± 7.1 kg) and six sheep (one‐year‐old and weighing 27.9 ± 2.7 kg) were used in this study, in a replicated 3 × 3 Latin square experiment. Total protozoa concentration was determined under the microscope; total fungi and methanogens were assessed using quantitative polymerase chain reaction and expressed as a percentage of total bacterial 16S rRNA gene copies; bacterial communities were investigated by targeted 16S rRNA gene (V3–V4 region) sequencing. The percentage of fungi was significantly higher in alpacas than in sheep under the LS diet, while the concentration of protozoa was significantly lower in alpacas under HS, MS and LS diets. The alpha diversity including Shannon, Chao l and ACE indices of bacterial communities was higher in alpacas than in sheep, under the LS diet. A total of 299 genera belonging to 22 phyla were observed in the forestomach of alpaca and sheep, with Bacteroidetes and Firmicutes dominating both animal species. Phyla Armatimonadetes and Fusobacteria, as well as 64 genera, were detected only in alpacas, whereas phyla Acidobacteria and Nitrospira, as well as 44 genera, were found only in sheep. The abundance of cellulolytic bacteria, including Butyrivibrio and Pseudobutyrivibrio, was higher in alpacas than in sheep under all three diets. These differences in the forestomach microbial communities partly explained why alpacas displayed a higher poor‐quality roughage digestibility, and a lower methane production. Results also revealed that the adverse effects of high‐concentrate diets (70%) were lesser in alpacas than in sheep.